Comparison of first and second waves of COVID-19 through severity markers in ICU patients of a developing country - Muhammad Sohaib Asghar; Farah Yasmin; Muhammad Nadeem Ahsan; Haris Alvi; Pahnwatt Taweesedt; Salim Surani (Greater Baltimore Medical Center, 2021)
Background: Many countries are experiencing outbreaks of the second wave of COVID-19 infection. With these outbreaks, the severity of the disease is still ambiguously projected. Certain inflammatory markers are known to be associated with the severity of the disease and regular monitoring of these biomarkers in intensive care unit admissions is paramount to improve clinical outcomes.Objectives: This study was aimed to compare the severity markers of the patients infected during the first wave versus the second wave in an intensive care unit.Methods: We conducted a retrospective study obtaining patient's data from hospital records, admitted during the first wave in March-May 2020, and compared the data with those COVID-19 patients admitted during the second wave from October-November 2020. A descriptive comparison was done among the patients admitted to intensive care unit (ICU) during both waves of the pandemic.Results: 92 patients from first wave and 68 patients from second wave were included in the analysis, all admitted to ICU with equal gender distribution. Increased age and length of ICU stay was observed during the first wave. BMI, in-hospital mortality and invasive ventilation were statistically indifferent between both the waves. There was significantly higher APACHE-II during first wave (p = 0.007), but SOFA at day 1 (p = 0.213) and day 7 of ICU stay remain indifferent (p = 0.119). Inflammatory markers were less severe during second wave while only neutrophils and lymphocytes were found to peak higher.Conclusion: Most of the severity markers were less intense during the early analysis of second wave.